Is there evidence for efficacy of human papillomavirus vaccination in solid organ transplant recipients? - Emeline Vinkenes; Martine A. Nielsen; Jan Blaakaer (Elsevier, 2019)
Human papillomavirus (HPV) infection is one of the most common sexually transmitted infections worldwide and is associated with precancerous lesions and cancers of the cervix, vulva, vagina, penis, anus, tonsils and base of the tongue. Several studies show an increased risk of HPV-associated cancers in solid organ transplant recipients (SOTR). The aims of this review are to investigate the evidence of efficacy for the HPV vaccination in transplant recipients and to discuss the known national guidelines. A systematic literature search has been conducted to identify studies where SOTR received the HPV vaccination to evaluate the efficacy of the HPV vaccine on this population. The primary outcome was antibody response against the HPV genotypes included in the vaccines and the secondary outcome was national guidelines recommending HPV vaccination of SOTR. Three cohort studies evaluated immunogenicity. Two studies found suboptimal effect of the HPV vaccine, while an early terminated study detected 100% seropositivity. We have identified four national guidelines in the following countries; United States of America, Canada, Australia and Ireland, along with a recommendation from the World Health Organization (WHO).The results from the three studies were inconclusive due to the small sample sizes and the diverging results. Recommendations of HPV vaccination of SOTR is based on the knowledge about safety and efficiency in the general population and the safety of other inactivated (not live) vaccines in SOTR. Theoretically, the nonavalent vaccine should be recommended as the first choice in SOTR without age- or sex restrictions. Keywords: Human papillomavirus vaccine, HPV vaccine, Solid organ transplant recipient, Immunocompromised, Immunogenicity, Guideline